2016
DOI: 10.1134/s1063784216060062
|View full text |Cite
|
Sign up to set email alerts
|

Ion drag as a mechanism of plasma dust structure rotation in a strata in a magnetic field

Abstract: In experiments on complex plasmas, afixed strata region in which the levitation of dust structures is observed is investigated using the method of probing by calibrated dust particles of different sizes in an applied magnetic field under elevated pressures. The measured azimuthal velocity of the probing particles corresponds to the action of the ion drag force for 4 μm-size particles and to the entrainment by the rotating gas owing to the electron vortex flow inside the strata for 1 μm-size particles. Extrapol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In this case, the rotation of the dust particles occurs under the drag force action by ions drifting in crossed magnetic (longitudinal) and electric (radial ambipolar) fields. This mechanism was studied in detail in a series of papers [17][18][19][38][39][40][41][42][43]. With the magnetic-field increase, the rotation velocity slows down and drops to zero, at B ≈ 0.027 T the rotation inversion occurs.…”
mentioning
confidence: 99%
“…In this case, the rotation of the dust particles occurs under the drag force action by ions drifting in crossed magnetic (longitudinal) and electric (radial ambipolar) fields. This mechanism was studied in detail in a series of papers [17][18][19][38][39][40][41][42][43]. With the magnetic-field increase, the rotation velocity slows down and drops to zero, at B ≈ 0.027 T the rotation inversion occurs.…”
mentioning
confidence: 99%
“…A number of studies have identified several physical phenomena associated with the dusty structures, their geometry, their dynamics in a magnetic field, and the ordering of particles. Nowadays, studies of dusty plasmas in magnetic fields continue, and the magnetic field magnitude range has been sufficiently widened .…”
Section: Introductionmentioning
confidence: 99%